2002
DOI: 10.1038/sj.bjc.6600211
|View full text |Cite
|
Sign up to set email alerts
|

The presence of bone marrow cytokeratin-immunoreactive cells does not predict outcome in gastric cancer patients

Abstract: The independent prognostic significance of isolated tumour cells in bone marrow is still a matter of debate. This study evaluated the possible association of bone marrow micrometastases with tumour progression and prognosis in patients affected by gastric cancer. Bone marrow aspirates from both iliac crests were obtained from 114 consecutive patients operated on for gastric cancer. The specimens were stained with monoclonal antibody CAM 5.2 which reacts predominantly with cytokeratin filaments 8 and 19. Among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Most published papers report an association between the presence of BMM and a poor prognosis, [5][6][7][8][9][10][11][12][13] though some other researchers have not demonstrated similar associations between BMM positivity and poor outcome. 22 So far, the most comprehensive micrometastasis research has been carried out in breast cancer. A meta-analysis with 4703 breast cancer patients showed that BMM at the time of diagnosis appeared to be a significant and independent predictor of a lower overall survival, breast cancer-specific survival, and distant disease-free survival after a median follow-up of 5.2 years.…”
Section: Discussionmentioning
confidence: 99%
“…Most published papers report an association between the presence of BMM and a poor prognosis, [5][6][7][8][9][10][11][12][13] though some other researchers have not demonstrated similar associations between BMM positivity and poor outcome. 22 So far, the most comprehensive micrometastasis research has been carried out in breast cancer. A meta-analysis with 4703 breast cancer patients showed that BMM at the time of diagnosis appeared to be a significant and independent predictor of a lower overall survival, breast cancer-specific survival, and distant disease-free survival after a median follow-up of 5.2 years.…”
Section: Discussionmentioning
confidence: 99%
“…Although Thorban et al identified BMMs as a significant prognostic indicator of poor survival on multivariate analysis 16 and Macadam et al demonstrated that BMMs were significant predictors of early recurrence, 17 other researchers have not demonstrated similar associations between BMM positivity and poor outcome. 19 Although these trials utilized an immunocytochemical technique similar to our own to identify BMMs, laboratory heterogeneity occurred due to variances in the actual antibodies used for BMM detection. Additionally, the patients recruited to the trial of Thorban et al exclusively represented patients with squamous cell carcinoma of the esophagus, and it is possible that these factors may contribute to why our findings differ from theirs.…”
Section: Discussionmentioning
confidence: 99%
“…Macadam et al [88] and Thorban et al [89] confirmed bone marrow micrometastases as an independent prognostic variable for both recurrence and survival by multivariate analysis. However, other studies failed to show a correlation between the presence of CK-positive cells in bone marrow and clinical outcome [90]. Differences in the choice of antibody, staining procedures, and cytological interpretation may partly explain these discrepant results.…”
Section: Mrd In Solid Tumorsmentioning
confidence: 96%